2016
DOI: 10.1016/s2095-3119(15)61201-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium and sulfur on antioxidants and physiological parameters of garlic plants during senescence

Abstract: A hydroponic study was conducted to determine the effects of selenium (Se: 0μmol• L −1 , 3μmol• L −1 , 6μmol• L −1 ) on senescence-related oxidative stress in garlic plants grown under two sulfur (S) levels. We evaluated the yields of plants harvested at 160 and 200 days after sowing. Plants grown under a low-Se dose (0.3 μmol•L −1 ) at low S level showed higher yields (12.0% increase in fresh weight yield, 13.7% increase in dry weight yield) than those of controls, despite a decrease in chlorophyll concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The Se doses tested were 1.0 and 0.9 mg kg -1 of soil, respectively. The growth-promoting effect of Se may be attributable to its antioxidant properties (Cheng et al, 2016). The negative or positive effect of Se over the plant growth depends on its concentration (Fargasova, 2004).…”
Section: Effect Of Se On Fresh Weight Of Garlic Organsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Se doses tested were 1.0 and 0.9 mg kg -1 of soil, respectively. The growth-promoting effect of Se may be attributable to its antioxidant properties (Cheng et al, 2016). The negative or positive effect of Se over the plant growth depends on its concentration (Fargasova, 2004).…”
Section: Effect Of Se On Fresh Weight Of Garlic Organsmentioning
confidence: 99%
“…Additionally, Se reduces the rate of protein synthesis because the substitution of SeMet for Met is less effective as a substrate for peptide bond formation during translocation (Eustice et al, 1981). On the other hand, the formation of Se-amino acids increases the ethylene production (Cheng et al, 2016). This phytohormone produces changes in the membrane lipid composition and increases membrane permeability that could affect the plant tissues (Xue et al, 2001).…”
Section: Effect Of Se Biofortification On Other Nutrients Of Garlic Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in H 2 O 2 concentrations caused by the activity of other enzymes (e.g., CAT and APX) may have provided an environment where there was no stimulus for SOD synthesis. Some studies have already shown that Se negatively impacts SOD activity in plants Xue and Hartikainen, 2000;Cheng et al, 2016;Reis et al, 2018).…”
Section: Antioxidant Metabolism Responsementioning
confidence: 99%
“…In the present study, a 3 g Se ha −1 solution of selenate and 3 g S ha −1 sulphate as well as a combination of both elements clearly caused to stimulate the biomass of alfalfa plant. The application of Se in plants increases biomass accumulation (Cheng et al, 2016) or yield (Põldma et al, 2013). Growth-promoting Se effects have been reported in lettuce (Xue et al, 2001), ryegrass (Hartikainen et al, 1997;Hartikainen & Xue, 1999), and soybean (Djanaguiraman et al, 2005).…”
Section: Discussionmentioning
confidence: 98%